2017
DOI: 10.1097/hcr.0000000000000225
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics Predictive of Cardiac Rehabilitation Adherence

Abstract: Purpose Cardiac rehabilitation (CR) is a program of structured exercise and interventions for coronary risk factor reduction that reduces morbidity and mortality following a major cardiac event. Although a dose response relationship between number of CR sessions completed and health outcomes has been demonstrated, adherence with CR is not high. In this study we examined associations between number ofsessions completed within CR and patient demographics, clinical characteristics, smoking status, and socioeconom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
30
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 41 publications
(44 reference statements)
7
30
1
3
Order By: Relevance
“…Our analysis showed that socioeconomic disadvantage is an important correlate of adherence to PR. Similar results have been reported for cardiac rehabilitation, with patients of lower socioeconomic status and current smokers attending three times fewer sessions than patients without such risk factors (39). In our study, patient characteristics predictive of lowest adherence to PR were White race, smoking, and low baseline functional capacity, which may be indicative of health-related barriers to following the exercise regimen.…”
Section: Discussionsupporting
confidence: 87%
“…Our analysis showed that socioeconomic disadvantage is an important correlate of adherence to PR. Similar results have been reported for cardiac rehabilitation, with patients of lower socioeconomic status and current smokers attending three times fewer sessions than patients without such risk factors (39). In our study, patient characteristics predictive of lowest adherence to PR were White race, smoking, and low baseline functional capacity, which may be indicative of health-related barriers to following the exercise regimen.…”
Section: Discussionsupporting
confidence: 87%
“…And finally, in the secondary prevention group were more smokers than in the primary prevention group. Smoking has previously been reported as inconsistently related to inactivity among CVD patients [20, 42], but is associated with increased symptoms of depression levels [19]. Smoking was therefore also treated as a potential confounder in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Patient factors, such as socioeconomic status, depression, age, gender, and race are consistently strong predictors of CR engagement (number of sessions attended and completion rates). 1–4 These factors could be impacted by a more flexible scheduling model that could minimize barriers such as transportation issues and time limitations that are also predictive of poorer program engagement. 3–6 For example, a recent qualitative systematic review and meta-analysis of patient barriers to CR engagement concluded that scheduling was a major factor due to transportation issues and competing social and occupational demands, especially among women.…”
Section: Introductionmentioning
confidence: 99%